IDENTIFIKASI POLA CORE-PERIPHERY DI KAWASAN PERKOTAAN CEKUNGAN BANDUNG - Saepulloh, Asep; Uny, Chivilya; Mokobombang, Sitty Rukmini; Joyodiningrat, M. Henry (KURVATEK, 2025)
This study identifies the core-periphery pattern and distribution of core-periphery areas in the Bandung Basin Urban Area (KPCB), covering Bandung City, Cimahi, Bandung Regency, West Bandung, and parts of Sumedang. Analysis methods included Rank Spearman, Weighted Overlay, and spatial-statistical analysis using PODES 2018 data and satellite imagery. Rank Spearman results show that Population Density has the strongest correlation (40% weight), followed by Main Source of Income (30%), Land Use (20%), and Slope (10%). Weighted Overlay analysis reveals the dominance of core areas in the east and north, and periphery areas in the south and west, influenced by population density, infrastructure and settlements. Spatial autocorrelation showed a cluster pattern (z-score >2.58; Moran's Index 0.197). Cluster & Outlier Analysis confirms the core cluster is centered in Bandung and Cimahi with expansion to the east, north, and south, while the periphery is dominant in the west. The results are in line with Presidential Regulation No 45/2018, which establishes Bandung and Cimahi as urban cores with potential expansion to the surrounding areas. This pattern reflects structured development with resource access gaps between the core and periphery.